The status of trauma registry systems in Chinese hospitals. Issue 6 (13th October 2011) - Fitzharris, Michael; Zhong, Wang; Myburgh, John; Xuezhong, Yu; Yu, James; Hammond, Naomi; Finfer, Simon R; Taylor, Colman; Wu, Yangfeng
Abstract : Injuries are a major source of mortality and morbidity in China with approximately 66 million citizens requiring emergency medical care. Trauma registries provide the basis for quality assurance processes and inform the treatment of the injured patient. Against the backdrop of the recently established Chinese National Injury Surveillance System, the feasibility of establishing a multicentre trauma registry in a limited number of hospitals was examined. Seven hospital directors reported on a range of hospital characteristics including patient volume information and the types of patient information routinely collected. The findings indicate significant numbers of patients presenting due to injury, though little comparability in the type of information collected both between hospitals and with international trauma registry systems. The development of multicentre trauma registry is suggested as a way to monitor trauma system performance. The integration of clinical indicators into the National Injury Surveillance System in the long term is also recommended.